Handbook of research on telecommunications planning and management for business - Lee, In, 1958-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This book provides original, in-depth, and innovative articles on telecommunications policy, management, and business applications"--Provided by publisher.
Section 6. Telecommunications Network Design -- 54. Network Planning and Dimensioning for Broadband Access to the Internet Regarding Quality of Service Demands -- 55. Overlay Networks: New Techniques for Global Service and Network Provisioning -- 56. Optimising P2P Networks by Adaptive Overlay Construction -- 57. Designing a New Service Overlay on a Carrier Network Using the Efficient Frontier -- 58. Combining Small and Large Scale Roaming Parameters to Optimize the Design of PCS -- 59. Secure Resource Optimization in Distributed Service Computing -- 60. Trends, Optimization and Management of Optical Networks -- Compilation of References.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Keywords: Telecommunication; Telecommunication policy; Telecommunication systems -- Management; Automated fault management in wireless networks; Convergence of the Internet and telecommunications; Digital convergence and home network services; Dynamics of mobile service adoption; High-speed multimedia networks; Knowledge management implementation; Modeling intrusion detection; Next generation access networks; Role of organizational culture; Spectrum management policy; Telecommunication customer demand management; Telecommunications business management; Telecommunications network design; Wireless community networks; Electronic books